THE EFFECT OF REAL EARNINGS MANAGEMENT ON THE VALUE RELEVANCE OF EARNINGS, BOOK VALUE OF EQUITY, AND CASH FLOW FROM OPERATIONS - Rasyid, Muhammad Arief; Subekti, . Imam (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study investigates the impact of real earnings management on value relevance of earnings, book value of equity, and cash flow from operations. The study uses price model i.e. stock price as firm value. The real earnings management is measured by abnormal cash flow of operation (Abn.CFO), abnormal cash production costs (Abn.PROD), and abnormal cash discretionary expenses (Abn.DISCR) as real earnings management proxy. The sample of this study is manufacturing sector companies listed in Indonesian Stock Exchange (IDX). Regression analyses on a sample of 312 firm-years from 2011 to 2013 are employed to test hypotheses. The result of the test shows that earnings, book value of equity, and cash flow from operations are relevant to measure firm value. The value relevance decreased when firms engaged in real earnings management. This is because real earnings management will reduce the quality of the financial statements. When the financial statements do not have good quality, then users will prefer to use other reports that are more relevant in making a decision. Key words: earnings, book value of equity, cash flow from operation, stock price, abnormal cash flow of operation, abnormal production cost, and abnormal discretionary expenses.